Complete mitochondrial genome sequence of Squalidus chankanensis tsuchigae (Cypriniformes: Cyprinidae). Issue 1 (2nd January 2020) - Park, So Young; Kim, Sang Ki; Sagong, Jin; Ryu, Shi-Hyun; Yu, Jeong-Nam
Abstract: We determined the complete mitochondrial genome sequence of Squalidus chankanensis tsuchigae (Cypriniformes: Cyprinidae). It is 16, 603 bp long, with 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNA genes, and 1 control region, which is 927 bp long, located between tRNApro and tRNAphe. The overall base composition is as follows: 29.98% A, 16.86% G, 25.44% T, and 27.72% C, with a slight AT bias. These results provide necessary data for phylogenetic studies on Squalidus species.